2009
DOI: 10.1124/jpet.109.154146
|View full text |Cite
|
Sign up to set email alerts
|

Mutation-Specific Potency and Efficacy of Cystic Fibrosis Transmembrane Conductance Regulator Chloride Channel Potentiators

Abstract: Cystic fibrosis (CF) is caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) ClϪ channel. The mutations G551D and G1349D, which affect the nucleotidebinding domains (NBDs) of CFTR protein, reduce channel activity. This defect can be corrected pharmacologically by small molecules called potentiators. CF mutations residing in the intracellular loops (ICLs), connecting the transmembrane segments of CFTR, may also reduce channel activity. We have investigated the extent of loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 39 publications
(48 reference statements)
4
41
0
Order By: Relevance
“…Small molecule correctors (aminoarylthiozoles, quinazolinylaminopyrimidinones and bisaminomethylbithiazoles) have been shown to have varying effects on CF epithelia dependent upon the mutation [50]. The idea of mutation specific correctors was verified by Caputo et al [51] whose results suggested that felodipine and the phenyglycine PG-01, exerted a wider pharmacological effect (acting on CFTR mutations E193K, G970R and G551D) compared to the lesser potentiative sulfonamide SF-01. More recently, the newest CFTR corrector, VX-770, has been described in vitro to increase CFTR channel open probability in recombinant cells expressing mutated CFTR ( F508 and G551D) and to increase chloride secretion in human CF bronchial epithelia [52].…”
Section: +mentioning
confidence: 61%
“…Small molecule correctors (aminoarylthiozoles, quinazolinylaminopyrimidinones and bisaminomethylbithiazoles) have been shown to have varying effects on CF epithelia dependent upon the mutation [50]. The idea of mutation specific correctors was verified by Caputo et al [51] whose results suggested that felodipine and the phenyglycine PG-01, exerted a wider pharmacological effect (acting on CFTR mutations E193K, G970R and G551D) compared to the lesser potentiative sulfonamide SF-01. More recently, the newest CFTR corrector, VX-770, has been described in vitro to increase CFTR channel open probability in recombinant cells expressing mutated CFTR ( F508 and G551D) and to increase chloride secretion in human CF bronchial epithelia [52].…”
Section: +mentioning
confidence: 61%
“…These included derivatives of 1,4-dihydropyridine and phenylglycine which potentiated G551D-, G970R-, and G1349D-CFTR to a similar extent as ivacaftor [23,[25][26]. In contrast, sulfamoyl-4-oxoquinoline-3-carboxamides were weakly effective on G551D-, G970R-, and G1349D-CFTR [26] and phloxine B strongly potentiated G551D-CFTR, but not G1349D-CFTR [22].…”
Section: Discussionmentioning
confidence: 78%
“…These included derivatives of 1,4-dihydropyridine and phenylglycine which potentiated G551D-, G970R-, and G1349D-CFTR to a similar extent as ivacaftor [23,[25][26]. In contrast, sulfamoyl-4-oxoquinoline-3-carboxamides were weakly effective on G551D-, G970R-, and G1349D-CFTR [26] and phloxine B strongly potentiated G551D-CFTR, but not G1349D-CFTR [22]. Previous studies have speculated that these differences may be due to distinct binding sites which may be differentially altered by CFTR mutations or which may modulate CFTR channel gating through different mechanisms [22][23]26].…”
Section: Discussionmentioning
confidence: 96%
“…CF potentiators promote surface channel activity but do not promote folding and/or trafficking of the nascent polypeptide. Importantly, the potentiator drug Vertex 770 (http://www.cff.org/research/ClinicalResearch/ FAQs/VX-770/) (Caputo et al 2009;Van Goor et al 2009;Wellhauser et al 2009;Moran 2010) has recently completed a Phase II clinical trial with the G551D mutant (Fig. 3A), which is trafficked from the ER normally, cell surface localized but lacks channel activity.…”
Section: Cf Therapeutics and The Pnmentioning
confidence: 99%